Protection Capacity of Kaffir Lime (Citrus hystrix) Peel Extract Against Dengue Haemorrhagic Fever Mosquitoes - Joni Hendri (Jurnal Sain Veteriner, 2013)
Abstract The use of chemicals as mosquitos repellent may cause health problems. Extract of caffir lime (Citrus hystrix) as mosquitoes can be used as another option.The present study was aimed to analyze the protection capacity of C. hystrix against Aedes aegypti and Ae. albopictus. The experimental study using completely randomized design was done. The obtained data were calculated using the protection capacity formula and analyzed using t-test. The result indicated that protection capacity of Citrus hystrix extract for 6 hours on average gave 34.82% of protection against Ae. aegypti and 41,44% of Ae. albopictus.The caffir lime extract has been able to reject the mosquitoes, Ae. aegypti and Ae. albopictus. Although the thrust of the caffir lime is not as good as chemical products, butit can be used as alternative mosquitoes repellent.